Case report: a case of lung squamous cell carcinoma with a novel FGFR3-IER5L fusion mutation responding to anlotinib - Chen, Xiaoting; Zhao, Wen; Yu, Hejiang; Wang, Shuang; Wang, Chengjun; Song, Yanan; Meng, Xue; Li, Jisheng (Frontiers in Oncology, 2024)
Lung squamous cell carcinoma (LUSC) is the second most common pathological type of non-small cell lung cancer (NSCLC). However, compared with lung adenocarcinoma (LUAD), the incidence of driver gene mutations in LUSC is relatively lower and treatment options for LUSC patients are very limited. We described a LUSC patient with a novel FGFR3-IER5L fusion revealed by next generation sequencing in this report. The patient refused surgery, radiotherapy or chemotherapy and received anlotinib treatment. Anlotinib is a small molecular multi-target tyrosine kinase inhibitor, which can inhibit the activity of kinases including vascular endothelial growth factor receptor 2/3 (VEGFR2/3), fibroblast growth factor receptor 1-4 (FGFR1-4), platelet-derived growth factor receptor α/β (PDGFRα/β), and c-Kit. The patient achieved partial response and the progression-free survival was 3.8 months.